Linking Microbial Community Succession With Substance Transformation in a Thermophilic Ectopic Fermentation System - Wen, Ping; Wang, Yueqiang; Huang, Wenfeng; Wang, Weiwu; Chen, Tao; Yu, Zhen (Frontiers in Microbiology, 2022)
Ectopic fermentation system (EFS) is an effective technology for treating mass livestock manure. However, the associations between microbial communities and substance transformation remain controversial. This study aimed to investigate chicken manure EFS lasting 170 days using 16S rRNA sequencing and electrochemical, spectroscopic, and chromatographic analyses. The results showed a noticeable transformation of protein-like substances into humus-like substances. Meanwhile, the electron–accepting capacity increased persistently, effectively reflecting the humification of organic substances. The contents of phenols that promoted electron transfer continued to increase from 2.80% to 6.00%, which could be used as a maturity indicator for EFS. During the heating period, the dominant microbial communities were Chloroflexi and Proteobacteria, whereas thermotolerant bacteria Cyanobacteria and Planctomycetes were significantly enriched from 1.64% to 50.15% during the continuous thermophilic period of EFS. The correlation analysis manifested that these thermotolerant bacteria were the major functional bacteria for the formation of phenols and the key to driving the humification of organic substances. This study provided insights into understanding the humification mechanisms and implementing regulatory strategies.